Investigation on the maximum power point in solar panel characteristics due to irradiance changes - Abdullah, Muhammad Amirul; Toha, Siti Fauziah; Ahmad, Salmiah (Institute of Physics (IOP) Publishing, 2017)
One of the disadvantages of the photovoltaic module as compared to other renewable resources is the dynamic characteristics of solar irradiance due to inconsistency weather condition and surrounding temperature. Commonly, a photovoltaic power generation systems consist of an embedded control system to maximize the power generation due to the inconsistency in irradiance. In order to improve the simplicity of the power optimization control, this paper present the characteristic of Maximum Power Point with various irradiance levels for Maximum Power Point Tracking (MPPT). The technique requires a set of data from photovoltaic simulation model to be extrapolated as a standard relationship between irradiance and maximum power. The result shows that the relationship between irradiance and maximum power can be represented by a simplified quadratic equation.